2022
DOI: 10.1111/joor.13355
|View full text |Cite
|
Sign up to set email alerts
|

Immediate curative effects of exercise therapy in patients with myalgia of the masticatory muscles

Abstract: Background: Exercise therapy is occasionally considered as an initial treatment for temporomandibular disorders. However, pain can be exacerbated during exercise therapy.Objective: To investigate the immediate curative effects of exercise therapy in patients with masticatory muscle myalgia.Methods: Fifty-nine patients with masticatory muscle myalgia were included.Therapists performed exercise therapy (stretched the painful masseter and/or cervical muscles along the direction of muscle contraction) in 10 rounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Jaw-opening exercises are the standard exercise therapy for TMDs. Several studies have shown that jaw-opening exercises are effective in decreasing muscle and joint pain and restoring TMJ mobility [ 8 , 9 , 10 ]. However, almost all studies evaluated the effectiveness of jaw-opening exercises, and, to date, no study has examined the effect of jaw-opening exercises on strength and duration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jaw-opening exercises are the standard exercise therapy for TMDs. Several studies have shown that jaw-opening exercises are effective in decreasing muscle and joint pain and restoring TMJ mobility [ 8 , 9 , 10 ]. However, almost all studies evaluated the effectiveness of jaw-opening exercises, and, to date, no study has examined the effect of jaw-opening exercises on strength and duration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%